-7=-3p+15-3p

Simple and best practice solution for -7=-3p+15-3p equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7=-3p+15-3p equation:


Simplifying
-7 = -3p + 15 + -3p

Reorder the terms:
-7 = 15 + -3p + -3p

Combine like terms: -3p + -3p = -6p
-7 = 15 + -6p

Solving
-7 = 15 + -6p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '6p' to each side of the equation.
-7 + 6p = 15 + -6p + 6p

Combine like terms: -6p + 6p = 0
-7 + 6p = 15 + 0
-7 + 6p = 15

Add '7' to each side of the equation.
-7 + 7 + 6p = 15 + 7

Combine like terms: -7 + 7 = 0
0 + 6p = 15 + 7
6p = 15 + 7

Combine like terms: 15 + 7 = 22
6p = 22

Divide each side by '6'.
p = 3.666666667

Simplifying
p = 3.666666667

See similar equations:

| X=18+-1.5y | | sin15=x/4000 | | (3x-10)=(3x-20) | | (X-2)+7x=180whatisx | | (6-z)(4z-2)=0 | | (6-2)(4z-2)=0 | | W-5/2=7/2 | | (X-2)+7x=180 | | (5x-12)=(x+54) | | 30x-(12x+500)= | | (2x+30)=(3x+5) | | -2w(w+9)(w+2)=0 | | 3(-2x+7)=-6x-2 | | (24-2)+7*24=180 | | 9x-35=14x | | -9x+2x-6x=0 | | 19(1+X)=16x-11 | | 6j=3+5j | | 12b=-12b | | 2h+9=3h | | (-2x+92)=(x+8) | | -5+4k=9k | | 4y-2(y+5)=0 | | 7v=-9+6v | | (4x+30)=(-2x+54) | | a-3=45 | | 10+4w=6w | | -5x+8x-4x=0 | | 9+9y=8y | | -5x+8x=0 | | -5p=-8+3p | | -[7x-(3x+4)]=-5-[4(2x-4)-2x] |

Equations solver categories